2022
DOI: 10.3390/agronomy12081731
|View full text |Cite
|
Sign up to set email alerts
|

Rice Momilactones and Phenolics: Expression of Relevant Biosynthetic Genes in Response to UV and Chilling Stresses

Abstract: Momilactones A (MA) and B (MB) are known as phytoalexins which principally play a role in the rice defense system against pathogens. This is the first study revealing that MA and MB contribute to rice tolerance to environmental stresses, including ultraviolet (UV) radiation and chilling conditions. The proofs were achieved by scrutinizing the responses of rice under stresses through the expression of relevant biosynthetic genes to momilactones (MRBG) and phenolics (PRBG) and their accumulation. Accordingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…On the other hand, the highest TFC (11.06 mg RE/g DW) was detected in B2, while the lowest TFC (2.54 mg RE/g DW) was found in A2. Previous studies indicated that TPC and TFC increased in rice seedlings under salinity effects [ 38 , 39 , 40 ], which might be due to the upregulation of genes encoding the major biosynthetic enzymes (e.g., phenylalanine ammonia lyase and chalcone synthase) in plant responses to biotic stresses [ 33 , 41 , 42 ]. In this study, TPC and TFC were remarkably stimulated in treatments with 75 mM salinity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the highest TFC (11.06 mg RE/g DW) was detected in B2, while the lowest TFC (2.54 mg RE/g DW) was found in A2. Previous studies indicated that TPC and TFC increased in rice seedlings under salinity effects [ 38 , 39 , 40 ], which might be due to the upregulation of genes encoding the major biosynthetic enzymes (e.g., phenylalanine ammonia lyase and chalcone synthase) in plant responses to biotic stresses [ 33 , 41 , 42 ]. In this study, TPC and TFC were remarkably stimulated in treatments with 75 mM salinity.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the differences in genetic diversity among tested rice varieties. In fact, different rice varieties (tolerant and susceptible cultivars) exhibit dissimilar mechanisms in phenolic accumulation to cope with stress conditions [ 33 , 38 , 39 , 40 ]. On the other hand, the present study revealed a notable decrease in the quantities of these phenolics in GBR when exposed to extreme levels of salinity (150 mM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations